(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
Eco-innovation enables efforts to change dominant linear business models of production and consumption into a resource-efficient circular economy model by transforming the way consumers interact with products and services, developing the process of change that can underpin a future resource-efficient society and economy. The EU’s Eco-Innovation Observatory defines eco-innovation as any new significantly improved product (goods or services), process, organisational change or marketing solution that reduces the use of natural and decreases the release of harmful substances across the product’s full lifecycle. Although, the ultimate need for eco-innovation is widely recognized within the EU, eco-innovation performance indicates high variations across EU Member States. European Eco-Innovation scoreboard groups countries into eco-innovation leaders, average eco-innovation performers and countries catching up in eco-innovation. Countries catching up in eco-innovations are mostly new Member States, just like Croatia. Therefore, this paper highlights the economic, environmental and social dimensions of eco-innovation in Croatia according to the Eco-innovation index. Results of the overall eco-innovation performance measured through 16 indicators grouped into five thematic areas in the period 2013-2017 confirmed there is no long-term involvement in fostering transition toward a resource-efficient economy. Modest results indicate that eco-innovation development and transition into a new resource-efficient economy model in Croatia is at an early stage. Accelerating eco-innovation in the economy and society needs to be one of Croatia’s priorities in order to boost a greener and more sustainable economy with potential to generate economic growth and new jobs.